Predisposing Factors for 30-Day Complications Following Leg Amputation. Issue 1 (January 2022) - Safavi, Kiya Shazadeh; Villarreal, Joseph; Hussien, Doha; Panchbhavi, Vinod K.; Jupiter, Daniel
Category: Trauma; Ankle; Diabetes; Other Introduction/Purpose: While amputation rates and amputation-related morbidity and mortality have been established for select populations, the impact of general demographic factors on postoperative surgical complications remains little studied. This study aims to analyze the influence of numerous demographic variables on specific surgical complications. Methods: We extracted data from the American College of Surgeons' National Surgical Quality Improvement Program database from 2012 to 2017 and searched for leg amputations using CPT codes 27881, 27882, 27884, and 27886, identifying 4, 162 patients. The association of 29 demographic variables with 4 complications (surgical infection, additional service, deep vein thrombosis [DVT], and sepsis) was analyzed using t tests or chi-squared tests. A logistic regression allowed determination of independent risk factors for each outcome, based on results from the bivariate analyses. Variables found to have P < 0.2 on bivariate analysis were subsequently included in the multivariate analysis of the corresponding surgical complication. Results: Preoperative open, 'contaminated, ' or 'dirty/infected' wounds, longer intraoperative times, development of sepsis prior to surgery, and admission of patients directly from home or from another hospital's emergency room were found to influence postoperative surgical infection rates. An individual's height, weight, total length of hospital stay, ethnicity, the presence of preoperative open or infected wounds, and wounds classified as 'dirty/infected' preoperatively affected postoperative additional service incidence. Preoperative congestive heart failure and large decreases in body weight, as well as a patient's total length of hospital stay, influenced postoperative DVT rates. A patient's preoperative functional heath status, total length of hospital stay, amputations conducted as emergency cases, as well as preoperative acute renal failure, open or infected wounds, sepsis, 'contaminated' or 'dirty/infected' wounds, impacted postoperative sepsis rates. Conclusion: Understanding these risk factors may allow providers to anticipate and address higher rates of complications in certain patient populations.